Performing arts and rurality: The search for the spirit of the territory (Cadernos de Sociomuseologia, 2022)
This article is based on ethnographic fieldwork conducted in a Portuguese community located in northern Portugal that shares its daily life with a theatre company. This research is theoretically grounded in the intersection between cultural heritage and memory studies that are used as pillars to capture the spirit of this territory. By gathering in their leisure time around theatre and other artistic experiences, this group of people activates a sense of belonging to the community through the sharing of practices and knowledge. The episodes described in this article were captured over two years through a series of interviews and participatory activities. The activities performed were videotaped and, as a whole, take part in a larger project aimed at building a virtual museum. More than an archive or repository composed of material objects of this theatre company, this museum experience is built from a collection of memories of this diverse inter-municipal community that coexists daily with artistic experiences that aggregate and challenge the sensibility of the population.Keywords: Participatory Ethnography, Performing Arts, Community, Cultural Heritage and Memory